(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Hypertension is one of the most common conditions affecting the health worldwide and is also the leading cause of death around the globe. There is a persistent need for effective nurse led intervention for interrupting the further spreading roots of the hypertension in the community. There is also a great need for creating awareness, ensuring the compliance with the treatment, modification of lifestyle and improving the quality of life for the sufferers of this condition. Methods: The study design was systematic review and it includes studies from databases of PUBMED, MEDLINE, Cochrane library, SCOPUS, Science direct, and Google scholar (2008-2019). The included studies were focusing on the management of hypertension among hypertensive adults in terms of awareness, treatment compliance, life style and quality of life. Result: The data was grouped and analyzed in terms of meta-analysis. Total 20 relevant articles were undertaken. Abstracted information is related to study design, population characteristics, intervention and outcomes. Conclusion: The nurse led intervention in the management of hypertension is an effective strategy in improving the health outcomes in terms of creating awareness, ensuring the compliance with the treatment, modification of life style and improving the quality of life among hypertensive adults.